(untitled) (JURNAL ADMINISTRASI PUBLIK, 2020)
The purpose of this study was to study participatory planning for development in the village of Sangkub I, Sangkub District, North Bolaang Mongondow District (Village Fund). This study used a quantitative method. Research respondents were 74 informants in Sangkub I village, Sangkub District, Bolaang Mongondow Regency North, instruments and data collection techniques used are questionnaires and structured interviews (quide interviews), analytical techniques used to test the hypothesis of simple statistical analysis or product moment chore, ask for positive and significant influence on development, which means that participatory planning variables are factors be the determinant or determinant of development; 2) The more well-planned participatory planning, the higher the level of development improvement, especially in Sangkub I Village, Sangkub District, Bolaang Mongondow Utara Regency. Kata Kunci : Participatory Planning, Development Effectiveness, Village